Genome-Wide Identification of Calcium-Dependent Protein Kinases in Chlamydomonas reinhardtii and Functional Analyses in Nitrogen Deficiency-Induced Oil Accumulation - Li, Yajun; Fei, Xiaowen; Dai, Haofu; Li, Jiangyue; Zhu, Weiju; Deng, Xiaodong (Frontiers in Plant Science, 2019)
Calcium-dependent protein kinases (CDPKs) are recognized as important calcium (Ca2+) sensors in signal transduction, and play multiple roles in plant growth and developmental processes as well as in response to various environmental stresses. However, little information is available about CDPK family in a green microalga Chlamydomonas reinhardtii. In this study, total 15 CrCDPK genes were identified in C. reinhardtii genome and their function in nitrogen-deficiency induced oil accumulation were analyzed. Our results showed that all of CrCDPK proteins harbored typical EF-hand Ca2+ binding domains and protein kinase domains. Phylogenetic analysis revealed that these CrCDPKs were cluster into one groups together with a subclade of several CPKs from Arabidopsis and rice, clearly separating from the remaining AtCPKs and OsCPKs. These genes were located in 10 chormosomes and one scaffold of C. reinhardtii and contained 6-17 exons. RNA sequencing and qRT-PCR assays indicated that most of these CrCDPKs were significantly induced by nitrogen (N) deficiency and salt stresses. Lanthanum chloride (LaCl3), a plasma membrane calcium channel blocker, limited oil accumulation in C. reinhardtii under N deficiency conditions, suggesting that Ca2+ was involved in the N deficiency-induced oil accumulation. Furthermore, RNAi silencing analyses demonstrated that 6 CrCDPKs played positive roles and 3 CrCDPKs played negative roles in N deficiency-induced oil accumulation in C. reinhardtii, respectively